Optimalisasi Teknik Ekstraksi dan Isolasi DNA Tanaman Suren (Toona Sureni Merr.) untuk Analisis Keragaman Genetik berdasarkan Random Amplified Polymorphic DNA (RAPD) - Restu, Muh; Mukrimin, Mukrimin; Gusmiaty, Gusmiaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2012)
The species of trees have different secondary compounds that need optimum extraction techniques. Appropriate extraction techniquesdetermine the quality and quantity of DNA produced. This research aims to found optimal of extraction methods and DNA isolation, thento created genome DNA in high quality and quantity, so that it can be using for genetic variation analyses in Suren (Toona sureni Merr.) byRandom Amplified Polymorphic DNA (RAPD). This study shows that DNA concentrates were 763.3 μg/ml, 180.0 μg/ml, 383.3 μg/ml, and436.7 μg/ml. While based on the results of PCR amplification using the primers OPD 03 shows that the four extraction methods used, the extraction method of number 3 has been able to produce genomic DNA with better quality and more number of bands, although the quantityis lower.